Preputial reconstruction after traumatic avulsion in a dog - Huppes, R. R.; Sprada, A. G. [UNESP]; Uscategui, R. A.R. [UNESP]; Passos, B. L.S.; De Nardi, A. B. [UNESP]; Pazzini, J. M. [UNESP]; Castro, J. L.C.; Minto, B. W. [UNESP]; Vicente, W. R.R. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2016)
Extensive loss of preputial tissue can cause additional penile injuries and infections, therefore it should be treated promptly. Extensive lesions may require reconstrsuctive techniques and even partial or complete amputation of the penis. This paper report the case of male mongrel dog showing traumatic avulsion lesion in the pelvic limbs, inguinal and preputial region. An axial pattern flap from the limb that was later amputated due to severity of injury was used for the inguinal and preputial reconstruction. The flap technique used was successful in the reconstruction of prepuce without penile amputation and the patient was discharged 14 days later.
Keywords: Amputation; Flap; Reconstructive surgery; Trauma